Comprehending Interculturality and its Future Directions in English Language Teaching and Teacher Education in the Colombian Context - Bertha Ramos-Holguín (Asociación Colombiana de Profesores de Ingles, 2021)
Interculturality has to do with the personal relational aspects of caring about the other. In this sense, interculturality confronts and challenges untruths and stereotypes that deny the existence of diversity. This article aims to provide a comprehensive view of what interculturality means, as well as to contribute to current and future trends in the field of English language teaching and teacher education in Colombia. I present examples of intercultural practices as possibilities to understand and explore interculturality in ELT, and I share a review of studies that have undertaken this complex conception of interculturality.